2019
DOI: 10.3390/biom9080311
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides: The Double-Edge Sword of Neuro-Ectodermal Derived Tumors

Abstract: Gangliosides, the glycosphingolipids carrying one or several sialic acid residues, are mostly localized at the plasma membrane in lipid raft domains and implicated in many cellular signaling pathways mostly by interacting with tyrosine kinase receptors. Gangliosides are divided into four series according to the number of sialic acid residues, which can be also modified by O-acetylation. Both ganglioside expression and sialic acid modifications can be modified in pathological conditions such as cancer, which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 93 publications
(123 reference statements)
0
71
0
Order By: Relevance
“…We have previously demonstrated that ganglioside-containing exosomes, as well as vesicles prepared from extracted exosome lipids and ganglioside-containing model mixtures, accelerate the amyloid formation of α-synuclein, which is related to Parkinson's disease [8]. Ganglioside lipids have also been proposed to be relevant for other diseases, for example, Alzheimer's disease, Tay-Sachs disease, and cancer [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that ganglioside-containing exosomes, as well as vesicles prepared from extracted exosome lipids and ganglioside-containing model mixtures, accelerate the amyloid formation of α-synuclein, which is related to Parkinson's disease [8]. Ganglioside lipids have also been proposed to be relevant for other diseases, for example, Alzheimer's disease, Tay-Sachs disease, and cancer [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…MS/MS fragmentation of these O-acetylated gangliosides species showed that O-acetylation can occur both on the terminal and on the subterminal sialic acid of the ganglioside carbohydrate moiety [51]. To get further insight into the position of the O-acetyl group on the sialic acid residue, DMB-labeled sialic acid derivatives extracted from gangliosides from BC cells were analyzed by LC-ES-MS. 9-O-acetyl-N-acetyl-neuraminic acid was identified as the main O-acetylated sialic acid species expressed on gangliosides from BC cells [4,51].…”
Section: Analysis Of O-acetylated and Non-o-acetylated Gangliosides Smentioning
confidence: 96%
“…Within lipid rafts, gangliosides play an active role in regulating receptor tyrosine kinases and cell signaling pathways involved in a large number of biological processes including vesicular traffic, cell polarity, or cell proliferation [2,3]. Changes in ganglioside composition are observed in many cancers, especially from a neuroectoderm origin, which exhibit aberrant ganglioside profiles, and several ganglioside species are considered as tumor-associated carbohydrate antigens, usually associated with a poor prognosis of the patient [4]. Sialic acid residues can be also O-acetylated, increasing the structural heterogeneity of the oligosaccharide structures and modulating ganglioside functions.…”
Section: Introductionmentioning
confidence: 99%
“…Gangliosides such as GM3, GM2, GM1, and GD1 are expressed across many normal human tissues ( 6 , 10 12 ) and appear to have multiple biological functions, particularly cell recognition and regulation of membrane-bound signaling proteins such as epidermal growth factor receptor and vascular endothelial growth factor receptor ( 10 , 13 ). In contrast, expression of disialoganglioside GD2 in normal tissues is limited essentially to the central nervous system, peripheral sensory nerve fibers, dermal melanocytes, lymphocytes, and mesenchymal stem cells ( 12 , 14 , 15 ). Although disialoganglioside GD2 appears to participate in cell signaling, its function in normal cellular physiology has not been fully elucidated and therefore is not well-understood ( 16 ).…”
Section: Introductionmentioning
confidence: 99%